Color contrast and stability as key elements for effective warning signals - Arenas, Lina María; Troscianko, Jolyon; Stevens, Martin (Frontiers in Ecology and Evolution, 2014)
Vivid warning signals (aposematism) have evolved repeatedly throughout the animal kingdom. However, relatively few studies consider what makes an effective signal, such as in terms of preventing attack and promoting avoidance learning by predators. Signal form varies substantially among and sometimes within species, but there has also been apparent convergence on relatively few main color types. We aimed to determine why warning signals often combine red, orange, yellow and black colors, and specifically to determine whether these colors provide highly salient and reliable visual signals under a range of environmental conditions. Using digital image analysis, we modeled ladybird (ladybug) coloration to an avian visual system. We calculated the contrast of several different ladybird species against an average green background, based on predicted opponent color channel responses in bird vision. Our results suggest that longwave colors (i.e. red, orange) are more contrasting than colors such as blue, against green natural backgrounds. Moreover, these colors yield relatively unchanging (stable) signals throughout the day and under different weather conditions. These analyses show how aposematic signals have evolved under selection to be more effective by being more conspicuous and reliable to the visual system of their potential avian predators.